Implementing Whatsapp Video Calls for Listening and Speaking Class (Students’ Perception) - Wiranegara, Dian Arsitades; Az Zahra, A’i Mulyani (ELITE Association Indonesia, 2023)
ABSTRACT The use of technology and the dynamics of virtual and non-virtual learning as a form of mixed teaching and learning process has been developed and can also be practiced for English listening-speaking classes. Nonetheless, the use of this virtual learning needs to be selected in order to meet the necessity of using it in practice. This study aims to determine the perception of PKPBI students of the Informatics engineering of UIN Maulana Malik Ibrahim Malang on the use of video calls in the practice of English-speaking classes. This type of research is descriptive and qualitative. The data was obtained from questionnaires via google from 35 research subjects, namely PKPBI students of the Informatics Engineering of UIN Maulana Malik Ibrahim Malang class. They studied Listening and Speaking skills in the third semester of the 2021/2022 academic year. The data is processed using a Likert scale and is equipped with tables and pie charts. The result showed that (1) the use of video calls was easily used as well as accessible from the WhatsApp application, (2) the use of video calls was easier to use during practice and get corrections from friends and lecturers than other platforms, such as G-meet and zoom, and (3) video calls were more effectively used in the practice of speaking with a total number of a limited number of students while google meet is effectively used in the practice of group speaking in large groups/one class in a longer duration of time. Keywords: WhatsApp video calls, google meet, zoom & Intensive English class